The use of clozapine in adolescents: A case report - Hashim, A.H.; Pillai, S.K.; Nordin, A.S.A.; Kaur, M. (2011)
We report or a young adolescent diagnosed with early-onset schizophrenia and subsequently treated with clozapine. Clozapine is often used as the last line of treatment for patients with schizopirenia, even in the paediatric population. This report highlights the usefulness and challenges of using clozapine in adolescents with schizophrenia.